The Influence of Poverty on Economic Growth in Central Kalimantan - Rima Harati (Al-Muhasabah: Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This research aims to analyze the influence of poverty variables on GRDP in Central Kalimantan using the 2015-2023 period. The analytical tools used are simple linear regression and classical assumption tests. The results of the analysis explain that the poverty variable is -0.645 which is greater than the error degree of 0.05 which explains that the poverty variable does not have a significant influence on economic growth in Central Kalimantan. From the results of the classical assumption test, it is explained that the normality test shows that the research data is normally distributed, there is no multicollinearity, there are no symptoms of heteroscedasticity. It is concluded that increasing or decreasing poverty will not have an impact on economic growth. This is because economic growth in Central Kalimantan is predominantly influenced by potential resources, adequate technology, and a workforce that increases every year with the development of the economic sector in Central Kalimantan.